2004
DOI: 10.1089/acm.2004.10.819
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study to Examine the Effects of a Mindfulness-Based Stress-Reduction and Relaxation Program on Levels of Stress Hormones, Physical Functioning, and Submaximal Exercise Responses

Abstract: While the 8-week stress reduction program for women with heart disease did not show significant interactions between groups for resting levels of stress hormones, physical functioning, or submaximal exercise responses, there was a significant difference in breathing patterns between the 2 groups during exercise following the mindfulness-based stress-reduction program. There was also a trend for change in the intervention group in the resting levels of cortisol and physical function scores that was not seen in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…Finally, alcohol- and cocaine-dependent individuals have shown attenuation of self-reported anxiety and drug cravings during stress, with concomitant adaptive shifts in autonomic nervous system function, while remaining fully engaged with their experiences (25). One might expect associated normalization in plasma cortisol concentrations, as has been suggested by studies of individuals with heart disease and cancer who have undergone MT (121, 122), though these studies are yet to be reported. Together, these suggest that through acceptance of both mood- and drug-related ruminative thought patterns, MT may show increased efficacy in individuals with co-morbid MDD and SUDs, where other treatments fail.…”
Section: (Iii) Mechanism Of Action In Mindfulness Trainingmentioning
confidence: 90%
“…Finally, alcohol- and cocaine-dependent individuals have shown attenuation of self-reported anxiety and drug cravings during stress, with concomitant adaptive shifts in autonomic nervous system function, while remaining fully engaged with their experiences (25). One might expect associated normalization in plasma cortisol concentrations, as has been suggested by studies of individuals with heart disease and cancer who have undergone MT (121, 122), though these studies are yet to be reported. Together, these suggest that through acceptance of both mood- and drug-related ruminative thought patterns, MT may show increased efficacy in individuals with co-morbid MDD and SUDs, where other treatments fail.…”
Section: (Iii) Mechanism Of Action In Mindfulness Trainingmentioning
confidence: 90%
“…After attending a meditation intervention using a focus on Ujjayi breathing, it was found that healthy persons demonstrated a decrease in respiratory rate and an increase in expiratory time 15. A group of participants with heart failure who attended an MBSR intervention also demonstrated a decrease in respiratory rate at rest that was shown to be a result of prolonged expiratory time 16. Although these studies demonstrated a change in respiratory pattern along with improved function and quality of life, they did not measure mindfulness levels 15,16…”
Section: Discussionmentioning
confidence: 99%
“…We examined the feasibility and acceptability of a mindfulness meditation intervention for persons with COPD using the MBSR structure and determined preliminary effects on breathing parameters, anxiety sensitivity, level of mindfulness, and COPD symptom burden. It has been demonstrated that breathing timing parameters change in response to meditation at rest over time in healthy individuals15 and in individuals with heart failure 16. This change can perhaps be used as a measure of meditation uptake.…”
Section: Introductionmentioning
confidence: 99%
“…However, to our knowledge, the direct influence of promoting mindfulness in psychotherapists on their patients’ psychotherapeutic results has not been examined. Most studies evaluating techniques of psychotherapists concentrate exclusively on patient intervention [13,14,15,16,17,18]. Thus, the aim of this study was to assess whether the promotion of mindfulness, through daily Zen meditation, in psychotherapists in training (PiTs) influences the treatment results of their patients.…”
Section: Introductionmentioning
confidence: 99%